2006
DOI: 10.1111/j.1600-0404.2006.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic risk factors in ischemic stroke and migraine in children

Abstract: The possible role of prothrombotic factors in individual cases of pediatric stroke and migraine cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Increased plasma levels of its soluble forms may indicate loss of TM from the EC membrane and thus a procoagulant state [152], and the decrease of soluble TM levels may be considered favourable with respect to cardiovascular risk [153]. In 30 children after ischemic stroke were found increased levels of aCL, anti-β2GPI, and TM compared with healthy controls [154]. Experimental data showed that four of eighteen aCL antibodies, derived from NZB/WF1 mouse reacted with rabbit TM and induced down-regulation of TM on endothelial cells, followed by induction of thrombosis [155].…”
Section: Monocytesmentioning
confidence: 93%
“…Increased plasma levels of its soluble forms may indicate loss of TM from the EC membrane and thus a procoagulant state [152], and the decrease of soluble TM levels may be considered favourable with respect to cardiovascular risk [153]. In 30 children after ischemic stroke were found increased levels of aCL, anti-β2GPI, and TM compared with healthy controls [154]. Experimental data showed that four of eighteen aCL antibodies, derived from NZB/WF1 mouse reacted with rabbit TM and induced down-regulation of TM on endothelial cells, followed by induction of thrombosis [155].…”
Section: Monocytesmentioning
confidence: 93%
“…The role aPL play in migraine has been studied before, and there is evidence both for and against aPL involvement in children (9)(10)(11)(12) and adults (13)(14)(15)(16). Many of the studies reported to date were small and poorly controlled.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, repetitive SDs in pathological states are noxious to the brain, and may affect disease progression of certain vasculopathies. Further supporting the concept of microvascular occlusion triggering migraine attacks in susceptible brains, several reports describe an association of migraine with hypercoagulable and prothrombotic states, or persistent foramen ovale …”
Section: The Association Of Migraine and Chronic Vasculopathiesmentioning
confidence: 84%
“…Further supporting the concept of microvascular occlusion triggering migraine attacks in susceptible brains, several reports describe an association of migraine with hypercoagulable and prothrombotic states, or persistent foramen ovale. 5,[22][23][24][25][26][27] In summary, we applaud Dr. Sacco for discussing broader implications of the observed association between migraine and vascular diseases such as retinal vasculopathies and MI. We emphasize that clinical and experimental evidence at this time is stronger to support SD as a link between migraine and chronic vasculopathies.…”
Section: The Association Of Migraine and Mi/retinal Vasculopathymentioning
confidence: 91%